Safety and Pharmacokinetic Profiles of Long-Acting Injectable Antiretroviral Drugs for HIV-1 Pre-Exposure Prophylaxis: A Systematic Review and Meta-analysis of Randomized Trials - Lazarus, Gilbert; Wangsaputra, Vincent Kharisma; Christianto,; Louisa, Melva; Soetikno, Vivian; Hamers, Raph L. (Frontiers in Pharmacology, 2021)
Objectives To investigate the safety and pharmacokinetic profiles of long-acting injectable pre-exposure prophylaxis (LAI PrEP), notably cabotegravir (CAB-LA) and rilpivirine (RPV-LA), for the prevention of human immunodeficiency virus-1 (HIV-1) infection. Methods Eligible randomized trials of LAI PrEP in HIV-uninfected and/or healthy patients were included and assessed with the Revised Cochrane risk-of-bias tool for randomized trials. Whenever possible, a meta-analysis was performed for safety outcomes by using a random-effects model with risk ratios and their 95% confidence intervals as the common effect measure. The protocol was registered with PROSPERO CRD42020154772. Results Eight studies cumulating a total of 666 participants were included in this systematic review, where five (362 intervention-arm volunteers) and four trials (194 intervention-arm volunteers) investigated CAB-LA and RPV-LA, respectively. We found that both CAB-LA and RPV-LA were generally well-tolerated as their safety profiles were similar to that of placebo in terms of any adverse event (AE), serious AE, and AE-related withdrawals. Furthermore, pharmacokinetic analyses revealed favorable prospects in viral inhibitory activity of CAB-LA and RPV-LA. Intramuscular (IM) injection of CAB-LA 600 mg Q8W was superior to CAB-LA 800 mg Q12W in male participants, while the same was true for RPV-LA 1200 mg IM Q8W over other dosing regimens. Although these results are promising, further research is required to confirm the findings on RPV-LA as current evidence is limited. Conclusion CAB-LA and RPV-LA have promising safety and pharmacokinetic profiles. The preventive efficacy of these agents is being evaluated in Phase 3 trials.